Lactone monomers obtained by enzyme catalysis and their use in reversible thermoresponsive networks. Issue 18 (14th January 2020) - Farhat, Wissam; Biundo, Antonino; Stamm, Arne; Malmström, Eva; Syrén, Per‐Olof
ABSTRACT: Enzyme‐catalyzed transformations have a great potential in both the pharmaceutical and chemical industry to achieve complex and (stereo)selective synthesis under mild reaction conditions. Still, the implementation of biocatalysis in the prerequisite upgrading of inert synthons into activated monomers for polymer applications has not yet been fully realized. In this contribution, we show that scaled‐up synthesis of bicyclic norcamphor lactone using an engineered Baeyer–Villiger monooxygenase (BVMO) is feasible to reach complete conversion of the corresponding ketone in 24 h in shake‐flask. The lactone monomer obtained by enzyme catalysis was copolymerized with ε‐caprolactone via ring‐opening polymerization to study the impact of the additional ring on material properties. Moreover, four‐arm star‐like, homo and block copolymers were designed from ε‐caprolactone, ε‐decalactone, and norcamphor lactone and characterized for their structural and thermal properties. These newly explored macromolecules were functionalized with furan rings using the enzyme Candida antarctica lipase B which allowed the formation of thermolabile networks via the pericyclic reaction with bismaleimide by means of Diels–Alder chemistry. The bonding/debonding state of these star‐like based materials can be tuned by a suitable selection of thermal treatment. The temperature‐dependent reversibility was assessed by thermal analysis and solubility test. Our results presented here shed light on the high potential of the use of chemoenzymatic approaches in the synthesis of new functional materials with tuned physiochemical properties. © 2020 The Authors. Journal of Applied Polymer Science published by Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48949. Abstract : Chemoenzymatic catalysis was used in this work to activate bulky cyclic ketones toward ring‐opening polymerization. The newly explored polymers were used in the design of temperature sensitive functional materials.